The rise in the cross sectoral dispersion of earnings expectations during COVID-19 - Joost Bats; William Greif; Daniel Kapp (European Central Bank (ECB), 2022)
This paper documents a durable increase in the cross-sectoral dispersion of earnings expectations during the COVID-19 crisis. The rise in dispersion of earnings forecasts can be explained by the introduction of lockdown measures, which had a particularly adverse impact on the travel sector. Accordingly, in terms of earnings expectations, countries that are relatively independent of the travel sector were least affected by a tightening of lockdowns. At the same time, vaccinations have been a game changer: more stringent lockdown measures added far less to the cross-sectoral dispersion in earnings expectations once vaccines started to be rolled out in late 2020. Going forward, the dispersion in earnings expectations continues to stand at elevated levels.
Keywords: E44; G10; G12; 330; COVID-19; Earnings expectations; Cross-sectoral dispersion; Lockdown measures; Vaccinations